WAWASAN BUDAYA: LITERASI KEUANGAN DAN AKUNTANSI DI DAERAH PANTAI - Oktaviani Rita Puspasari; Amir Hamzah; Lia Dwi Martika (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2024)
ABSTRACT The aim of this research is to analyze the factors influencing financial literacy and accounting literacy among coastal community members. The population in this study consists of 520 respondents. The sampling technique employed is random sampling, with a sample size of 210 individuals from coastal communities. Data analysis is conducted using Structural Equation Model (SEM), and the analysis tool is the LISREL 9 software. The results indicate that financial attitudes, religiosity, and financial planning positively influence both financial literacy and accounting literacy. Furthermore, financial literacy has a positive impact on accounting literacy. The implications of this study underscore the importance of considering these factors when designing financial and accounting literacy programs tailored to empower coastal communities. Precision in policy measures and educational initiatives can be crafted to meet the specific needs of coastal communities, enhancing their understanding of financial and accounting matters and supporting economic growth and community resilience in the region. Keyword: Financial Attitude, Religiosity, Financial Planning, Financial Literacy, Accounting Literacy, Coastal Communities